Methods of Laboratory Work in Physics - Karshiboyev Shavkat; Raymova Marfuga Umirzakovna; Ochilova Ozoda Odilovna; Xalilov Sarvar Samadovich (Zien Journals, 2023)
This article discusses pedagogical aspects and features of laboratory work in physics. This is reflected in the presence of specific characteristics of teaching to various units of physics.
Keywords: pedagogy; pedagogical methods; lectures; laboratory classes